MODEL MEDIASI MOTIVASI KERJA PADA PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KEPUASAN KERJA - Kusmana, Agus; Ali, Syarif; Husniati, Renny; Supriadi, Yudi Nur; Aprianti, Siska (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyse the impact of leadership style and workload on job satisfaction, with work motivation serving as a mediating variable among employees of XYZ Institution. The research employs a quantitative approach, utilizing Structural Equation Modelling (SEM) and analysed using Smart PLS version 4.0 software. The sample consists of 40 employees selected through purposive sampling. The findings reveal that leadership style positively and significantly influences job satisfaction, while workload also has a significant effect on job satisfaction. Furthermore, work motivation mediates the relationship between leadership style and job satisfaction, as well as between workload and job satisfaction. Additionally, work motivation directly and significantly affects job satisfaction. This study contributes both theoretically and practically by highlighting the importance of effective leadership, optimal workload management, and enhanced work motivation in promoting employee job satisfaction. The novelty of this study lies in examining the role of work motivation mediation in the relationship between leadership style, workload, and employee job satisfaction in Institution XYZ of the Ministry of Finance of the Republic of Indonesia, which provides new insights into how work motivation can strengthen or reduce the influence of these factors in the context of the public sector in Indonesia. The findings serve as a foundation for developing managerial policies aimed at improving employee well-being and organizational performance within XYZ Institution